2019
DOI: 10.1097/jnr.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Testing of the Turkish Version of the Stroke Self-Efficacy Questionnaire

Abstract: Background When stroke survivors return to their lives in society, they often face issues such as physical or cognitive impairment, dependence on others, social isolation, and reduced self-esteem, which may lead to disastrous consequences in patients' self-perceived self-efficacy and self-confidence in everyday life. Self-efficacy plays an important role in the well-being of stroke patients. Accurate assessment of the stroke patients' self-efficacy by health professionals is critical to obtaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Third, there is a need to expand the validation process of this French version of the SSEQ for its use in a French-speaking context. Like the English [10], Turkish [62], Chinese [63], Portuguese [64], Danish [65], and Hausa [66] versions, it is important to complete the validation process of the SSEQ-F, which, through the results of our study, demonstrated concurrent validity with ACTIVLIM-Stroke (ρ = 0.81; p < 0.001), Abiloco-Benin (ρ = 0.72; p < 0.001), the IPAQ-AF (ρ = 0.65; p < 0.001), and the RNLI (ρ = −0.84; p < 0.001). On this occasion, the reliability and responsiveness will be tested in order to make available a fully validated French version of the SSEQ that can allow the measurement of self-efficacy among stroke patients in French-speaking countries of sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there is a need to expand the validation process of this French version of the SSEQ for its use in a French-speaking context. Like the English [10], Turkish [62], Chinese [63], Portuguese [64], Danish [65], and Hausa [66] versions, it is important to complete the validation process of the SSEQ-F, which, through the results of our study, demonstrated concurrent validity with ACTIVLIM-Stroke (ρ = 0.81; p < 0.001), Abiloco-Benin (ρ = 0.72; p < 0.001), the IPAQ-AF (ρ = 0.65; p < 0.001), and the RNLI (ρ = −0.84; p < 0.001). On this occasion, the reliability and responsiveness will be tested in order to make available a fully validated French version of the SSEQ that can allow the measurement of self-efficacy among stroke patients in French-speaking countries of sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire has undergone Rasch analysis to further evaluate its psychometric properties, and confirmed that the two subscales showed good construct validity and the items yielded satisfying results according to the requirements for Rasch analysis [13]. The SSEQ has been translated into several languages, including Danish, Portuguese, Turkish, Hausa, Italian, Brazilian, Chinese, and Arabic [3,6,9,[17][18][19][20][21][22][23]. These translations have overall been successful in their validation and cross-cultural adaptations.…”
Section: Introductionmentioning
confidence: 86%
“…Due to the sudden-onset nature of strokes, families are faced with a situation where they have to take care of the patient themselves without being fully prepared [ 3 , 4 ]. As most stroke survivors live in the community and require long-term assistance from family, caring for them induces long-term effects in both stroke survivors and their family caregivers [ 5 , 6 ]. The prevalence of caregiver burden has been found to be 25.0–46.0% [ 7 ] and that prevalence remains elevated for an indefinite period following stroke [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%